A layered perovskite heterojunction material for piezoelectric photocatalysis and its synthesis method and application
By constructing the S-type heterojunction of Bi4Ti3O12 and CoMoO4, the problems of insufficient visible light absorption and complex preparation of Bi4Ti3O12 are solved, efficient photocatalytic activity and carrier separation are achieved, and the degradation ability of organic pollutants is significantly improved.
Patent Information
- Application Number
- CN202411199811.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-29
AI Technical Summary
As a piezoelectric photocatalytic material, Bi4Ti3O12 has insufficient visible light absorption and high recombination rate of electron hole pairs, resulting in limited photocatalytic efficiency and complex preparation methods, which are not conducive to practical application.
By constructing the S-type heterojunction of Bi4Ti3O12 and CoMoO4, the low band gap and strong redox capacity of CoMoO4 are used, combined with the layered structure and spontaneous polarization effect of Bi4Ti3O12, the photocatalytic activity and interface charge separation efficiency are improved.
The light absorption of the fully visible spectrum is achieved, the photocatalytic activity and carrier separation efficiency is significantly improved, the recombination of electron hole pairs is reduced, the stability and reusability of materials are enhanced, and the organic pollutants are improved. degradation ability.
Smart Images

Figure CN118719080B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalysts, and in particular relates to a layered perovskite heterojunction material for piezoelectric photocatalysis, a synthesis method and an application thereof. Background Art
[0002] In catalytic reactions, the piezoelectric potential and optical properties are coupled to generate a long-range ordered driving force that can regulate the separation and transport of photogenerated carriers (electron-hole pairs) on the surface and in the bulk, thereby enhancing its performance. On the other hand, the piezoelectric potential can lead to the accumulation / depletion of charges inside the semiconductor, as well as the adsorption of external polar molecules or ions at both ends of the potential, resulting in energy band rearrangement. The main contribution of the piezoelectric potential to photocatalysis is to inhibit the combination of electron-hole pairs and extend the carrier lifetime. Therefore, in the development of photocatalytic technology, people have proposed and implemented piezoelectric-photocatalytic coupling to slow down the carrier recombination rate and improve catalytic activity.
[0003] Bi4Ti3O 12 It is a layered perovskite oxide with ferroelectric properties, composed of (Bi2O2) 2+ Layer and (Bi2Ti3O 10 ) 2- The pseudoperovskite layer is composed of alternating layers. This layered structure provides a suitable structure for the growth of ultrathin nanosheets, thereby shortening the charge migration distance and increasing the exposure of active sites. However, the problem of insufficient visible light absorption affects its photocatalytic activity. In addition, due to the coherent off-center displacement of titanium ions within the TiO6 octahedral unit, Bi4Ti3O 12 They show good spontaneous polarization effect and piezoelectric response, which is beneficial to the directional transfer of carriers. However, due to the aggregation of nanoplates, the spontaneous polarization in random directions will cancel each other out, resulting in the easy in-situ recombination of photogenerated electron-hole pairs in the bulk phase and the decrease of the total piezoelectric induction intensity. Furthermore, these Bi4Ti3O 12 The preparation methods of nanomaterials often involve complicated processes, which are not conducive to practical applications. 12 Coupling with semiconductors with matching band gaps, reducing nanoplate agglomeration by constructing heterojunctions, promoting directional carrier transfer and improving visible light absorption are effective strategies to improve their piezoelectric photocatalytic performance.
[0004] In short, by 12 When compressive strain is applied, the electrostatic shielding is destroyed and the piezoelectric effect is generated, thereby improving the photocatalytic efficiency. 12 It is considered to be the most promising piezoelectric photocatalytic material due to its high spontaneous polarization, high Curie temperature and high photochemical activity.12 The band gap is wide, the electron / hole recombination rate is high, the photocatalytic efficiency is limited, and the solar energy cannot be fully utilized. Therefore, it is necessary to develop Bi4Ti3O 12 Piezoelectric photocatalytic materials are of great significance.
[0005] By constructing a heterojunction, the Bi4Ti3O 12 One of the strategies to improve the performance of piezoelectric photocatalytic materials. For example, some studies have initially explored the construction of AgI / Bi4Ti3O 12 、Bi4Ti3O 12 / BiOCl、Bi 12 TiO 20 / Bi4Ti3O 12 、g-C3N4 / Bi4Ti3O 12 、CoO x / Bi4Ti3O 12 However, common heterojunction materials such as AgI, BiOCl, Bi 12 TiO 20 Semiconductors such as CoO and g-C3N4 have insufficient visible light absorption and short light absorption cutoff edges, and cannot cover the entire visible spectrum well. x With Bi4Ti3O 12 The band structure of Bi4Ti3O 12 The valence band edge of CoO is about 1.9 eV, and the conduction band edge is about -0.97 eV. x The valence band edge is about 1.3eV, and the conduction band edge is about -0.7eV. This wrapped band structure cannot effectively guarantee the improvement of interfacial electron transfer and photocatalytic efficiency.
[0006] CoMoO4 is a typical transition metal oxide. Due to its low band gap energy (2.1-2.8 eV), strong redox ability, easy manufacturing and low cost, it is widely used as a battery material, electronic component and catalyst. In particular, the super conductivity of CoMoO4 is conducive to receiving electron transfer from other semiconductors. In contrast, CoMoO4 has excellent catalytic activity and photochemical properties. Although its visible light absorption has an undulating peak at 400-600 nm, it still covers the entire visible spectrum. More importantly, the valence band edge and conduction band edge of CoMoO4 are at 2.35 eV and -0.36 eV, respectively. Bi4Ti3O 12 The high negative conduction band (CB) edge of CoMoO4 and the high positive valence band (VB) edge of CoMoO4 indicate that it is theoretically possible to 12CoMoO4 is deposited on the surface to construct an S-type heterostructure. Constructing an S-type heterojunction can combine the advantages of each component and improve its photocatalytic activity. 12 Combining them to construct an S-type heterojunction is expected to overcome the Bi4Ti3O 12 limitations and greatly improve its photocatalytic activity. Summary of the invention
[0007] The purpose of the present invention is to provide a method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis, so as to develop a layered perovskite heterojunction material with piezoelectric effect, higher interface charge separation efficiency, simple preparation method, better stability, reusability, and piezoelectric photocatalytic degradation of organic pollutants.
[0008] Another object of the present invention is to provide a layered perovskite heterojunction material for piezoelectric photocatalysis.
[0009] A third object of the present invention is to provide an application of a layered perovskite heterojunction material for piezoelectric photocatalysis.
[0010] The technical solution of the present invention is: (one)
[0012] A method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis, characterized by comprising the following steps:
[0013] A. A certain amount of tetrabutyl titanate and sodium hydroxide were dissolved in deionized water, and a certain amount of Bi(NO3)3·5H2O was added to the mixture after ultrasonic dispersion for 30 min. The mixture was stirred at 600 r / min for 30 min and then slowly transferred to a polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction. After the reactants were cooled, they were filtered, and the solid product was washed with deionized water and ethanol for 3-6 times, and dried to obtain the product Bi4Ti3O 12 ;
[0014] B. Weigh a certain mass of Bi4Ti3O 12 , Co(NO3)2·6H2O and Na2MoO4·2H2O were dispersed in deionized water, stirred at 600r / min for 10-12h under light-proof conditions, and then the solid sample was collected by filtration and placed in an oven to dry to constant weight. The sample was then placed in a muffle furnace for heating and calcination. After cooling to room temperature, the sample Bi4Ti3O 12 / CoMoO4, and a layered perovskite heterojunction material is obtained.
[0015] As a further improvement of the present invention, in step A, the mass ratio of tetrabutyl titanate, sodium hydroxide and Bi(NO3)3·5H2O is 0.525:5-6:1.
[0016] As a further improvement of the present invention, in step A, the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 18-22 hours.
[0017] As a further improvement of the present invention, in step A, the drying temperature is 60-80° C., and the drying time is 12-24 hours.
[0018] As a further improvement of the present invention, in step B, Bi4Ti3O 12 The mass ratio of Co(NO3)2·6H2O and Na2MoO4·2H2O is 0.5-1.2:1:0.6.
[0019] As a further improvement of the present invention, in step B, the drying temperature is 60-80°C.
[0020] As a further improvement of the present invention, in step B, during calcination, the temperature is increased to 400-600° C. at a heating rate of 2-5° C. / min and maintained for 2-4 h. (two)
[0022] A layered perovskite heterojunction material for piezoelectric photocatalysis is prepared by the above-mentioned method for synthesizing the layered perovskite heterojunction material for piezoelectric photocatalysis. (three)
[0024] A layered perovskite heterojunction material for piezoelectric photocatalysis is used in the application of piezoelectric photocatalytic degradation of pollutants.
[0025] Further, the contaminants include bisphenol A.
[0026] The beneficial effect of the present invention is that the present invention constructs a heterojunction to form Bi4Ti3O 12 By combining with CoMoO4, a piezoelectric photocatalytic layered perovskite heterojunction material Bi4Ti3O3 with piezoelectric effect, stronger interface carrier separation ability, light absorption range covering the entire visible spectrum, and higher catalytic activity was constructed. 12 / CoMoO4. CoMoO4 is a semiconductor catalytic material with fluctuation peaks at 400-600 nm, but the light absorption still covers the entire visible spectrum, and the band gap is narrow, but the charge separation efficiency of a single material is low; Bi4Ti3O 12 The material has a unique layered crystal structure, good spontaneous polarization effect and piezoelectric response, and is considered to be a piezoelectric photocatalytic material with good application prospects. 12 Combined with CoMoO4, Bi4Ti3O was successfully realized 12The photogenerated electron-hole pairs of the / CoMoO4 composite photocatalytic nanomaterials are separated at the heterojunction interface, avoiding the electron-hole recombination problem in the band gap of the single CoMoO4 catalytic nanomaterial. 12 Due to the coherent eccentric displacement of Ti ions in the TiO6 octahedral unit, the catalyst can be induced to produce piezoelectric properties. Its close contact with CoMoO4 can construct an S-type heterojunction, further promoting the effective separation of photogenerated carriers, reducing the recombination of electron-hole pairs, and greatly enhancing the carrier interface separation efficiency. At the same time, it solves the solubility problem of perovskite materials in water to a certain extent, and improves the reusability of the material. Under the action of external mechanical stress, the piezoelectric material Bi4Ti3O 12 Polarization occurs inside and generates a piezoelectric potential difference. When the piezoelectric effect is combined with photocatalysis, the polarized charges in the piezoelectric material induce the generation of a polarized electric field, which can promote the migration and separation of photogenerated charges. The construction of a heterojunction can more effectively enhance the charge separation and electron transfer at the heterojunction interface, greatly improving the photocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Bi4Ti3O prepared in Example 1 of the present invention 12 / SEM image of CoMoO4;
[0028] Figure 2 Bi4Ti3O prepared in Example 1 and Comparative Examples 1 and 2 of the present invention 12 / CoMoO4、Bi4Ti3O 12 , UV diffuse reflectance absorption spectrum of CoMoO4;
[0029] Figure 3 Bi4Ti3O prepared in Example 1 and Comparative Examples 1 and 2 of the present invention 12 / CoMoO4、Bi4Ti3O 12 , Fourier diffuse reflectance infrared spectrum of CoMoO4;
[0030] Figure 4 Bi4Ti3O prepared in Example 1 and Comparative Examples 1 and 2 of the present invention 12 / CoMoO4、Bi4Ti3O 12 , Performance comparison of CoMoO4 piezoelectric photocatalytic degradation of bisphenol A;
[0031] Figure 5 Bi4Ti3O prepared in Example 1 of the present invention 12 / CoMoO4 piezoelectric photocatalytic degradation of bisphenol A reusable experimental degradation diagram. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0033] Embodiment 1,
[0034] A method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis comprises the following steps:
[0035] A. Dissolve 0.84g of tetrabutyl titanate and 9.6g of sodium hydroxide in 30mL of deionized water, and add 1.6g of Bi(NO3)3·5H2O to the mixture after ultrasonic dispersion for 30min. Stir continuously for 30min at 600r / min and then slowly transfer to a 50mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction, and keep at 180℃ for 20h. After the reactant is cooled, filter it, wash the solid product with deionized water and ethanol for 6 times, and dry it in an oven at 60℃ for 24h to obtain the product Bi4Ti3O 12 ;
[0036] B. Weigh 0.73g Bi4Ti3O 12 , 1.46 g Co(NO3)2·6H2O and 0.876 g Na2MoO4·2H2O were dispersed in 60 mL deionized water, stirred at 600 r / min for 12 h under light-proof conditions, and then the solid sample was collected by filtration and placed in an oven at 60 °C to dry to constant weight. The sample was then placed in a muffle furnace for heating and calcination at a heating rate of 5 °C / min to 500 °C and maintained at 500 °C for 3 h. After cooling to room temperature, the sample Bi4Ti3O 12 / CoMoO4, and a layered perovskite heterojunction material is obtained.
[0037] Figure 1 Bi4Ti3O prepared in Example 1 12 SEM image of / CoMoO4. Figure 1 As shown, Bi4Ti3O 12 / CoMoO4 composite photocatalytic nanomaterial is a layered stacked nanosheet structure.
[0038] Comparative Example 1
[0039] Only the catalyst Bi4Ti3O was prepared 12 :
[0040] 0.84 g of tetrabutyl titanate and 8.8 g of sodium hydroxide were dissolved in 30 mL of deionized water. After ultrasonic dispersion for 30 min, 1.6 g of Bi(NO3)3·5H2O was added to the mixture. After continuous stirring at 600 r / min for 30 min, the mixture was slowly transferred to a 50 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction and maintained at 160 °C for 22 h. After the reactants were cooled, they were filtered, and the solid product was washed with deionized water and ethanol for 6 times, and dried in an oven at 80 °C for 18 h to obtain the product Bi4Ti3O 12 .
[0041] Comparative Example 2
[0042] Only the catalyst CoMoO4 was prepared:
[0043] 1.0 g Co(NO3)2·6H2O and 0.6 g Na2MoO4·2H2O were respectively weighed and dispersed in 60 mL deionized water. After being fully stirred at 600 r / min for 10 h under light-proof conditions, the solid sample was collected by filtration and placed in an oven at 80°C to dry to constant weight. The sample was then placed in a muffle furnace for heating and calcination at a heating rate of 4°C / min to 600°C and maintained at 600°C for 2 h. After cooling to room temperature, the product CoMoO4 was obtained.
[0044] Embodiment 2,
[0045] A method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis comprises the following steps:
[0046] A. Dissolve 0.84 g of tetrabutyl titanate and 8.4 g of sodium hydroxide in 30 mL of deionized water, and add 1.6 g of Bi(NO3)3·5H2O to the mixture after ultrasonic dispersion for 30 min. Stir continuously for 30 min at 600 r / min and then slowly transfer to a 50 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction, and keep at 160 ° C for 22 hours. After the reactant is cooled, filter it, wash the solid product with deionized water and ethanol for 5 times, and dry it in an oven at 70 ° C for 12 hours to obtain the product Bi4Ti3O 12 ;
[0047] B. Weigh 1.095g Bi4Ti3O 12, 1.46 g Co(NO3)2·6H2O and 0.876 g Na2MoO4·2H2O were dispersed in 60 mL deionized water, stirred at 600 r / min for 10 h under light-proof conditions, and then the solid sample was collected by filtration and placed in an oven at 80 °C to dry to constant weight. The sample was then placed in a muffle furnace for heating and calcination at a heating rate of 3 °C / min to 600 °C and maintained at 600 °C for 3 h. After cooling to room temperature, the sample Bi4Ti3O 12 / CoMoO4, and a layered perovskite heterojunction material is obtained.
[0048] Embodiment 3,
[0049] A method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis comprises the following steps:
[0050] A. Dissolve 0.84 g of tetrabutyl titanate and 8.0 g of sodium hydroxide in 30 mL of deionized water, and add 1.6 g of Bi(NO3)3·5H2O to the mixture after ultrasonic dispersion for 30 min. Stir continuously for 30 min at 600 r / min and then slowly transfer to a 50 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction, and keep at 200 ° C for 18 hours. After the reactant is cooled, filter it, wash the solid product with deionized water and ethanol for 4 times, and dry it in an oven at 80 ° C for 18 hours to obtain the product Bi4Ti3O 12 ;
[0051] B. Weigh 1.752g Bi4Ti3O 12 , 1.46 g Co(NO3)2·6H2O and 0.876 g Na2MoO4·2H2O were dispersed in 60 mL deionized water, stirred at 600 r / min for 11 h under light-proof conditions, and then the solid sample was collected by filtration and placed in an oven at 80 °C to dry to constant weight. The sample was then placed in a muffle furnace for heating and calcination at a heating rate of 2 °C / min to 400 °C and maintained at 400 °C for 4 h; after cooling to room temperature, the sample Bi4Ti3O 12 / CoMoO4, and a layered perovskite heterojunction material is obtained.
[0052] 1. Evaluation of photocatalytic degradation performance
[0053] The photocatalytic degradation performance of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 was evaluated as follows:
[0054] Mechanical vibration was provided by an ultrasonic cleaner (40 kHz, 100 W, Jielimei, Kunshan, China), and visible light irradiation (λ>420 nm, Beijing Zhongjiao Jinyuan Technology Co., Ltd.) was simulated by a 300 W xenon lamp. Before irradiation, a solution (100 mL) containing catalyst (0.1 g / L) and pollutant (5 mg / L) was placed in a beaker and mechanically stirred for 30 min in the dark to reach adsorption-desorption equilibrium. The beaker was then placed in an ultrasonic cleaner, and ultrasonic vibration (US) and simulated sunlight (SL) were turned on. Ice bags were placed in the ultrasonic cleaner to maintain the temperature at 25 ± 5 °C. At given time intervals (2.5 min for the first sampling and every 5 min thereafter), 1 mL of the solution was taken and immediately filtered with a 0.22 μm syringe filter for detection. The concentration of bisphenol A (BPA) was measured by HPLC (Shimadzu, LC-16) using an Agilent SB-C18 column (2.1 mm × 100 mm, 1.8 μm), a UV detector at 278 nm, and a mobile phase of acetonitrile and ultrapure water in a volume ratio of 50:50. The relative concentration (C / C0) was used to calculate the degradation efficiency.
[0055] Figure 2 Bi4Ti3O prepared in Example 1 and Comparative Examples 1 and 2 12 / CoMoO4、Bi4Ti3O 12 、UV diffuse reflection absorption spectrum of CoMoO4. Figure 2 As shown, Bi4Ti3O 12 The light absorption edge of CoMoO4 is about ~400nm, which means that it has insufficient absorption of visible light. However, CoMoO4 has strong absorption in the entire visible spectrum, and even though it has fluctuation peaks in the 400-600 nm absorption band, it still has a considerable absorption tail peak. 12 / CoMoO4, it can be seen that CoMoO4 and Bi4Ti3O 12 The composite effectively enhances the visible light absorption of the material, indicating that the two form complementary light absorption, which is beneficial to improving the visible light capture efficiency.
[0056] Figure 3 Bi4Ti3O prepared in Example 1 and Comparative Examples 1 and 2 12 / CoMoO4、Bi4Ti3O 12 , Fourier diffuse reflectance infrared spectrum of CoMoO4. 12 , the compound is at about 571cm -1 The absorption peak at 821 cm -1The absorption peaks observed at are related to the stretching and bending vibrations of Bi-O. These observations confirm the successful synthesis of Bi4Ti3O 12 For CoMoO4, at 479cm -1 The absorption peak at 581 cm -1 The absorption peak at 670 cm-1 corresponds to the stretching vibration of -CoO6. -1 The absorption peak at 704 cm -1 、786cm -1 、847cm -1 The absorption peak at 936 cm -1 The peak at corresponds to the vibration mode of -MoO4. 12 The main typical absorption peaks are present in Bi4Ti3O 12 / CoMoO4 samples, which further indicates that Bi4Ti3O 12 / CoMoO4 composite catalyst was successfully synthesized.
[0057] Figure 4 Bi4Ti3O prepared in Example 1 and Comparative Examples 1 and 2 12 / CoMoO4、Bi4Ti3O 12 , CoMoO4 piezoelectric photocatalytic degradation of bisphenol A performance comparison chart. The experimental results show that: under the conditions of catalyst dosage of 0.1 g / L, initial bisphenol A concentration of 5 mg / L, and initial temperature of room temperature, single Bi4Ti3O 12 The degradation rate of bisphenol A under piezoelectric catalysis was 34.23%, which indicates that the internal polarization electric field formed by the asymmetric center induced by external mechanical stress causes electrons to transfer quickly to the surface of the pollutant, which means that the single Bi4Ti3O 12 It is a piezoelectric catalytic material with good performance; single Bi4Ti3O 12 The degradation rate of bisphenol A under visible light catalysis was 3.52%, indicating that its visible light catalytic efficiency was low; under photocatalysis or piezoelectric photocatalysis, the degradation rates of bisphenol A by single CoMoO4 were 45.03% and 49.77%, respectively, which showed that single CoMoO4 had relatively considerable photocatalytic activity but no obvious piezoelectric catalytic effect, and the removal effect was poor due to the rapid in-situ recombination of carriers; while Bi4Ti3O 12The degradation efficiency of the Bi4Ti3O4 composite material for pollutants reached 98.73% within 20 min under the action of piezoelectric-visible light catalysis, which indicates that the photogenerated electrons migrated rapidly across the heterojunction interface under the action of the polarization electric field, further accelerating the degradation efficiency of pollutants. 12 The photodegradation efficiency of pollutants by the / CoMoO4 composite material is still 82.36%, which means that the construction of the heterojunction greatly improves the interface charge transfer efficiency.
[0058] 2. Continuous degradation experiment
[0059] After the first degradation reaction of the catalyst prepared in Example 1 was completed, the post-reaction solution was centrifuged and washed, and the recovered catalyst was dried in a freeze dryer for 48 h, and then put into the reactor again for the next degradation experiment. Except for the materials, the other degradation reaction conditions were consistent with the first photocatalytic degradation performance evaluation experiment setting procedure; after the second reaction was completed, the above steps were repeated to carry out three degradation experiments.
[0060] Figure 5 Bi4Ti3O prepared in Example 1 12 / CoMoO4 piezoelectric photocatalytic degradation of bisphenol A reusable experimental degradation diagram. Figure 5 As shown in the figure, the degradation rate of bisphenol A was above 95% in three consecutive degradation experiments, which indicates that Bi4Ti3O 12 The photocatalytic activity of / CoMoO4 photocatalytic nanomaterials still remains good after three cycles.
[0061] The present invention Bi4Ti3O 12 The pollutants degraded by piezoelectric photocatalysis of the / CoMoO4 layered perovskite heterojunction material include but are not limited to bisphenol A, carbamazepine, atrazine, tetracycline, rhodamine B, etc. Preferably, Bi4Ti3O 12 / CoMoO4 has an exceptionally good degradation effect on bisphenol A under piezoelectric photocatalytic conditions. On the one hand, under visible light irradiation, the photocatalytic material Bi4Ti3O 12 / CoMoO4 are photoexcited to generate photogenerated electrons and photogenerated holes under visible light irradiation. The matching energy level positions make the photogenerated electrons in the conduction band of CoMoO4 transfer to Bi4Ti3O across the heterojunction interface. 12 This S-type charge transport mechanism not only promotes carrier separation but also retains strong redox ability. On the other hand, under the mechanical stress of ultrasonic vibration, the piezoelectric catalytic material Bi4Ti3O 12 The unidirectional polarization electric field is generated, which leads to the formation of a polarization charge layer at the contact interface with the photocatalytic material CoMoO4 and induces the piezoelectric catalytic material Bi4Ti3O12 The surface energy band is bent, which further induces the electrons to migrate from CoMoO4 to Bi4Ti3O 12 , the electron transfer across the interface will effectively inhibit the recombination of electron-hole pairs and significantly improve the charge separation efficiency. Eventually, the pollutants are oxidized by surface active oxygen or hydroxyl groups and holes, and finally generate water and carbon dioxide.
Claims
1. A method for synthesizing layered perovskite heterojunction materials for piezoelectric photocatalysis, characterized in that The following steps are involved: A. Dissolve tetrabutyl titanate and sodium hydroxide in deionized water, add Bi(NO3)3·5H2O to the mixture after ultrasonic dispersion, continue stirring and perform hydrothermal reaction, filter, wash and dry the reactants after cooling to obtain the product Bi4Ti3O 12 ; B. Weigh Bi4Ti3O 12 , Co(NO3)2·6H2O and Na2MoO4·2H2O were dispersed in deionized water, stirred thoroughly under light-proof conditions, filtered to collect solid samples, dried to constant weight, and then the samples were calcined at elevated temperatures. After cooling to room temperature, samples Bi4Ti3O 12 / CoMoO4, and a layered perovskite heterojunction material is obtained.
2. The method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis according to claim 1, characterized in that: In step A, the mass ratio of tetrabutyl titanate, sodium hydroxide and Bi(NO3)3·5H2O is 0.525:5-6:
1.
3. The method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis according to claim 1, characterized in that: In step A, the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 18-22 h.
4. The method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis according to claim 1, characterized in that: In step A, the drying temperature is 60-80°C and the drying time is 12-24h.
5. The method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis according to claim 1, characterized in that: In step B, Bi4Ti3O 12 The mass ratio of Co(NO3)2·6H2O and Na2MoO4·2H2O is 0.5-1.2:1:0.
6.
6. The method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis according to claim 1, characterized in that: In step B, the drying temperature is 60-80°C.
7. The method for synthesizing a layered perovskite heterojunction material for piezoelectric photocatalysis according to claim 1, characterized in that: In step B, during calcination, the temperature is increased to 400-600°C at a heating rate of 2-5°C / min and maintained for 2-4 hours.
8. A layered perovskite heterojunction material for piezoelectric photocatalysis, characterized in that: The material is made by the synthesis method of a layered perovskite heterojunction material for piezoelectric photocatalysis according to any one of claims 1 to 7.
9. Use of the layered perovskite heterojunction material for piezoelectric photocatalysis according to claim 8 in piezoelectric photocatalytic degradation of pollutants.
10. The use of the layered perovskite heterojunction material for piezoelectric photocatalysis in piezoelectric photocatalytic degradation of pollutants according to claim 9, characterized in that: The contaminants include bisphenol A.
